Construction and application of procedural pathways combined with information management in nursing staff skills training system - Liping Cui; Yuting Dong; Shan Zhang; Wenxia Ma; Min Li (BMC Medical Education, 2024)
Abstract Objective To explore the application effect of procedural pathways combined with information management in the construction of nursing staff skills training system. Methods This was a quasi-experimental study with a control group and an experimental group. A total of 300 newly admitted nurses or nurses who required training within three years of admission were selected as the experimental group, and 267 nurses who were trained in the same hospital during the same period in 2020 were selected as the control group. The experimental group received skills training using a system that combines procedural pathways with information management, while the control group received traditional teaching mode. The outcome measures included theoretical score, operation score, nurse competency, patient satisfaction, and nursing-related adverse events. The data were analyzed using t-test, chi-square test, and rank-sum test. Results The experimental group had higher scores in theoretical assessment, skills assessment, nurse competency, and patient satisfaction, and lower incidence of nursing-related adverse events than the control group (P < 0.05). Conclusion The strategy of procedural pathways combined with information management provides a new perspective and method for nursing operation skills training, effectively improves clinical nursing quality and ensures patient safety.